Integrating rainwater harvesting and greywater recycling to increase water efficiency in office buildings - Habibullah, Nurhazwani; Sahrir, Syazwani; Ponrahono, Zakiah (Malaysian Institute of Planners, 2023)
Water is an essential component of existence. It is one of the primary resources for maintaining a daily presence. Due to high demand, freshwater becomes limited; therefore, rainwater harvesting and greywater recycling should be implemented as an alternative to substituting freshwater consumption for non-potable activities. This study discusses the implementation of rainwater harvesting and greywater recycling and the contribution to water efficiency and the environment. The main objectives of this paper are to explicate the potential benefits of integrating rainwater harvesting and greywater recycling in office buildings and to elucidate the impact of water conservation from office buildings on the environment. The result shows that implementing both systems in buildings can reduce freshwater consumption, water saving, and the discharge of wastewater to the environment, which is an essential point for water efficiency. The findings can serve as a reference for stakeholders, as they can reduce the freshwater consumption for non-potable activities and increase the water efficiency of buildings, thereby alleviating freshwater scarcity in the future.